Designing A Supplementary Book of Descriptive and Narrative English Texts based on Local Wisdom - Rezza (Program Studi Pendidikan Bahasa Inggris IKIP PGRI Pontianak, 2020)
The choosing of teaching material became a factor that influenced students’ motivation in learning. The teaching material in the form of text in the textbook was not well known by students. It caused of the textbook contents were not authentic – students were not familiar with it. Developing a supplementary book especially for teaching descriptive and narrative text based on Local Wisdom in Rasau Jaya, Kabuapaten Kubu Raya was an aim in this research. The textbook which is constructed by the notion of local wisdom will help students to link their knowledge to the subject matter and preserve the local culture. The research design was a research and development then the final product is the Supplementary Book of Local Wisdom which focuses on descriptive and Narrative text using the ADDIE approach (Analysis, Design, Development, Implementation, and Evaluation) for grade X high school students according to the K 13 curriculum. The analysis will be carried out in several stages (1) requirements analysis, (2) ADDIE application, (3) Product testing, (4) revision, (5) product Testing, (6) Revision, and (7) final results. Furthermore, found in every test conducted, including content test 85.45%, 88.8% for design test, and 87.8% small group test. The results shown that this supplementary book was valid, reliable, and applied in using.